2014
DOI: 10.1017/s1368980014000676
|View full text |Cite
|
Sign up to set email alerts
|

Obesity – a risk factor for asthma, but not for atopic dermatitis, allergic rhinitis and sensitization

Abstract: Objective: To analyse the relationship between obesity and overweight and the prevalence of allergic diseases and sensitization, and the impact of gender and place of residence. Design: Questionnaire based on those used in ISAAC (International Study of Asthma and Allergies in Childhood) and ECRHS (European Community Respiratory Health Survey). Setting: Our study involved populations of the eight largest cities and one rural region in Poland (each with over 150 000 inhabitants). Subjects: The study included 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 22 publications
10
51
1
5
Order By: Relevance
“…Conversely, obesity was very uncommon, being found in only 4/253 (1.6%) of subjects. This finding did not confirm the previous studies which showed that obesity was associated with AD in adults [25,37], supporting the results of Sybilski et al which reported obesity as a risk factor for asthma but not for AD in a cohort of 18,617 subjects [30]. Further studies are needed to deeply clarify this relationship, since obesity was related to AD in adult women, but not in men [15].…”
Section: Discussioncontrasting
confidence: 63%
“…Conversely, obesity was very uncommon, being found in only 4/253 (1.6%) of subjects. This finding did not confirm the previous studies which showed that obesity was associated with AD in adults [25,37], supporting the results of Sybilski et al which reported obesity as a risk factor for asthma but not for AD in a cohort of 18,617 subjects [30]. Further studies are needed to deeply clarify this relationship, since obesity was related to AD in adult women, but not in men [15].…”
Section: Discussioncontrasting
confidence: 63%
“…86 Future studies are needed to better elucidate the role of these factors in the association between obesity and AD. Finally, only 4 of 28 studies analyzed did not rely on self-or parent-reported AD/ eczema; 3 used the Hanifin and Rajka criteria and 1 required at least 1 positive allergen-specific immunoglobulin E. 26,55,64,68 The use of questionnaires introduces potential recall and misclassification bias, because AD may clinically mimic other eczematous processes, such as contact and nummular dermatitis. Nevertheless, the ISAAC questionnaire used in most of the self-reported studies has been validated and used widely in epidemiologic studies regarding allergy in children.…”
Section: Discussionmentioning
confidence: 99%
“…After review of the titles and abstracts, 536 articles did not meet our inclusion criteria, and 12 were excluded 31-42 for a lack of data for the frequency of AD/eczema or BMI classification. In total, 30 studies 26,33, were included in the review, of which 20 had valid data that could be pooled to assess for the effects of overweight, 26,43,47,50,[53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] 23 for obesity, 26,33,43,45,47,50,[52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] and 26 for overweight/obesity. 26,43,44,[46]…”
Section: Literature Searchmentioning
confidence: 99%
“…Studies of overweight or obesity and allergic rhinitis have predominantly included children and have yielded conflicting results 1422 . Whereas some studies reported that neither overweight nor obesity was associated with symptoms suggestive of allergic rhinitis in children 19 , others have shown a positive association between obesity and allergic rhinitis in children and young adults 2022 , with yet a few others showing an negative (inverse) association in school-aged children 14 and adult men 17 . Of interest, some studies have shown that obesity is only associated with an increased risk of allergic rhinitis in female subjects, raising the question of whether hormonal surges around puberty predispose adolescent girls to allergic sensitization and allergic rhinitis 20, 23 .…”
Section: Introductionmentioning
confidence: 99%